2015
DOI: 10.1038/bmt.2015.237
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pre-existing invasive aspergillosis on allo-HSCT outcome: a retrospective EBMT analysis by the Infectious Diseases and Acute Leukemia Working Parties

Abstract: Historically, invasive aspergillosis (IA) has been a major barrier for allogeneic hematopoietic stem cell transplantation (allo-HSCT). The influence of invasive IA on long-term survival and on transplant-related complications has not been investigated in a larger patient cohort under current conditions. Our aim was to analyze the long-term outcome of patients undergoing allo-HSCT with a history of prior IA. We used European Society for Blood and Marrow Transplantation database data of first allo-HSCTs performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
2
17
0
1
Order By: Relevance
“…However, recent studies have demonstrated a controversial point, e.g., a single-center study on behalf of CIC 725 suggested that IA prior to allo-HSCT did not impair the outcome of transplantation procedure with effective diagnosis and secondary prophylaxis of IFD, as reported at the 41 st Annual EBMT Meeting and 57 th Annual ASH Meeting in 2015 [18,19]. A retrospective EBMT analysis by the Infectious Diseases and Acute Leukemia Working Parties concerning influence of pre-existing invasive aspergillosis upon allo-HSCT outcome in acute leukemia patients (published online in October 2015 in Bone Marrow Transplantation) confirm our data that, in general, a history of IA should not be a contraindication when considering allo-HSCT in acute leukemia patients [20] [20]. So far, there are no available data on clinical effects of other then IA pre-existing IFD and in pediatric allo-HSCT recipients.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, recent studies have demonstrated a controversial point, e.g., a single-center study on behalf of CIC 725 suggested that IA prior to allo-HSCT did not impair the outcome of transplantation procedure with effective diagnosis and secondary prophylaxis of IFD, as reported at the 41 st Annual EBMT Meeting and 57 th Annual ASH Meeting in 2015 [18,19]. A retrospective EBMT analysis by the Infectious Diseases and Acute Leukemia Working Parties concerning influence of pre-existing invasive aspergillosis upon allo-HSCT outcome in acute leukemia patients (published online in October 2015 in Bone Marrow Transplantation) confirm our data that, in general, a history of IA should not be a contraindication when considering allo-HSCT in acute leukemia patients [20] [20]. So far, there are no available data on clinical effects of other then IA pre-existing IFD and in pediatric allo-HSCT recipients.…”
Section: Introductionsupporting
confidence: 80%
“…Firstly, our study included allo-HSCT recipients who have been transplanted over recent years, in comparison with published studies [13][14][15][16]20]. An overall better supportive care management was applied over last years, thus improving, specifically the outcome of allo-HSCT in patients with infectious complications including IFD.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, prior IFI has been shown to predict a poor prognosis in patients undergoing allo-HSCT [28,29]. Recently, the European Society for Blood and Marrow Transplantation analyzed long-term transplant outcomes in 1152 patients with pre-existing IFIs undergoing allo-HSCT and showed no significant impact of pre-existing IFIs on OS, relapse-free survival, aGVHD, or cGVHD [30]. Previous reports also suggested that pretransplant IFI is not a contraindication to allo-HSCT [9,11,31].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients may develop pulmonary IFD before transplantation, which could be associated with much more increased treatment‐related mortality and subsequent poorer survival, and IFD has thus been considered a relative contraindication to allo‐SCT. However, according to recent advances in diagnostic and therapeutic approaches to pulmonary IFD, an increasing number of patients who have experienced a prior episode of pulmonary IFD eventually undergo allo‐SCT . Although no optimal pretransplant strategy for those patients has been firmly established, some patients with non‐resolving lesions despite prolonged antifungal treatment or a cavity located near a large vessel may undergo surgical procedures (SP) with the intention of reducing the risk of fungal relapse or massive hemorrhage .…”
Section: Introductionmentioning
confidence: 99%